THE ROLE OF INDONESIA’S FEMALE PEACEKEEPERS IN UNITED NATIONS PEACEKEEPING OPERATIONS TO PROMOTE GENDER EQUALITY - Yulia Fadillah; Jonni Mahroza; Harangan Sitorus; Helda Risman (The Republic of Indonesia Defense University, 2020)
Women expand their feminist value to protect local societies from conflict impacts which put mostly women and children as victims, in line with the growth of women's capacity in peacekeeping operations. Women perform a significant role as peacekeepers in UN missions for peace and conflict resolutions to create a counterbalance in masculine dominance of UN Peacekeeping Operations based on UNSCR 1325. Women have played an important role as peacekeepers in the UN missions for peace and conflict resolution, to build trust among local communities especially women and children who are vulnerable to sexual harassment and violence. This paper will analyze the strategic role of Indonesia’s female peacekeepers in peace and conflict resolution under UN missions with a qualitative method in the concept of gender equality based on a phenomenological approach. This research finds that Indonesia’s female peacekeepers can provide approaches that can foster the inclusive peace process and become a role model for local women to achieve their right socially and politically. Indonesia’s female peacekeepers prove their vital part in fostering the achievement of peace and conflict resolution with a psychosocial approach that emphasizes psychological recovery and social development by Indonesian Peacekeeping Contingent under UN Missions.